STUDI KOMPARSI TERHADAP LAJU DISOLUSI TABLET PARASETAMOL DENGAN PENAMBAHAN POLISORBAT 80 - Najib, Ahmad (Jurnal Ilmiah As-Syifaa, 2010)
A study of the dissolution rate of paracetamol tablets using polysorbate 80 as wetting agent had been investigated. The aim of this investigation  is to determine  concentration of polysorbate 80 should be added to the formula to produced the tablet with the fastest dissolution rate.   The paracetamol tablets were prepared by wet granulation methods using polysorbate 80 with various concentration,   1%, 3%, 5%, 7% and 9% respectively. The tablet without polysorbate 80 was also prepared for comparison. The tablets had been evaluated with uniform size, uniform weight, hardness, disintegration time and the dissolution test.               The dissolution test of  tablet in phosphate buffer pH 5.8  using the stirring paddle  with rotation speed at 50 rpm at the temperature 37 ± 0.5°C. The release of paracetamol every time appointed well measured by UV spectrophotometer at wave length 242 nm and the concetration determinated with standard curve.            The evaluation of tablets showed that no one formula  suitable with requires, the hardness test only  formula I suitable with requires and the disintegration time all of the tablet suitable with requires. The result of statistical with complete random form method show the added of polysorbate 80 in the parasetamol tablets formula increase dissolution of paracetamol. The analysis efficiency dissolution using Duncan?s method on data?s showed that the concentration 3% of polysorbate 80 (formula III) give significant effect in increasing the dissolution rate of tablets ( a = 0.05 ).Key word : Polisorbat 80, Dissolition, Paracetamol